2021
DOI: 10.3390/s21248363
|View full text |Cite
|
Sign up to set email alerts
|

IoTactileSim: A Virtual Testbed for Tactile Industrial Internet of Things Services

Abstract: With the inclusion of tactile Internet (TI) in the industrial sector, we are at the doorstep of the tactile Industrial Internet of Things (IIoT). This provides the ability for the human operator to control and manipulate remote industrial environments in real-time. The TI use cases in IIoT demand a communication network, including ultra-low latency, ultra-high reliability, availability, and security. Additionally, the lack of the tactile IIoT testbed has made it more severe to investigate and improve the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Along similar lines, authors in [23] presented IoTactileSim as a virtual testbed that utilizes Mininet network emulator to create the network topology between the master and slave domains, as well as the tactile support engine. In addition, the CoppeliaSim robotic simulator was utilized to create a virtual teleoperator.…”
Section: Related Workmentioning
confidence: 99%
“…Along similar lines, authors in [23] presented IoTactileSim as a virtual testbed that utilizes Mininet network emulator to create the network topology between the master and slave domains, as well as the tactile support engine. In addition, the CoppeliaSim robotic simulator was utilized to create a virtual teleoperator.…”
Section: Related Workmentioning
confidence: 99%
“…In the tactile Internet, human beings will interact with machines in a physical and virtual space, whilst experiencing sensory emotions, forces and touch besides conventional video and audio data. Such advances in Internet technology, along with the fast evolution of communication techniques from the 1G to 6G, make possible emerging services such as machine‐to‐machine communication, H2MC, augmented and virtual reality in real time [59, 60].…”
Section: Basic Components Of the Ioementioning
confidence: 99%
“…The authors of [ 6 ] stressed the exigency of using a virtual testbed dubbed IoTactileSim to implement, investigate, and manage QoS provisioning in tactile industrial IoT (IIoT) services. The study demonstrated that tactile IIoT enables the real-time control and manipulation of remote industrial environments via a human operator.…”
mentioning
confidence: 99%